High risk of adverse birth outcomes among adolescents living with HIV in Botswana compared to adult women living with HIV and adolescents without HIV - Maya Jackson-Gibson; Rebecca Zash; Aamirah Mussa; Ellen C. Caniglia; Modiegi Diseko; Gloria Mayondi; Judith Mabuta; Chelsea Morroni; Mompati Mmalane; Shahin Lockman; Joseph Makhema; Roger L. Shapiro (BMC, 2022)
Abstract Background Adolescent girls are three times more likely to be living with HIV than boys of the same age. Prior studies have found associations between adolescent pregnancies and increased maternal morbidity and infant mortality, but few studies have assessed the impact of HIV infection on maternal and infant outcomes in adolescents. Methods The Tsepamo Study abstracts maternal and infant data from obstetric records in government maternity wards in Botswana. We assessed maternal complications and adverse birth outcomes for all singleton pregnancies from August 2014 to August 2020 at eighteen Tsepamo sites among adolescents (defined as 10-19 years of age) and adults (defined as 20-35 years of age), by HIV status. Univariate and multivariate logistic regression using a complete case analysis method were used to evaluate differences in outcomes. Results This analysis included 142,258 singleton births, 21,133 (14.9%) to adolescents and 121,125 (85.1%) to adults. The proportion of adults living with HIV (N = 22,114, 22.5%) was higher than adolescents (N = 1593, 7.6%). The proportion of most adverse birth outcomes was higher in adolescents. Among adolescents, those with HIV had increased likelihoods of anemia (aOR = 1.89, 95%CI 1.66, 2.15) and cesarean sections (aOR = 1.49, 95%CI 1.3,1.72), and infants with preterm birth (aOR = 1.15, 95%CI 1.0, 1.32), very preterm birth (aOR = 1.35, 95%CI 1.0,1.8), small for gestational age (aOR = 1.37, 95%CI 1.20,1.58), and very small for gestational age (aOR = 1.46, 95%CI 1.20, 1.79). Conclusions Adolescent pregnancy and adolescent HIV infection remain high in Botswana. Adolescents have higher risk of adverse maternal and infant birth outcomes than adults, with the worst outcomes among adolescents living with HIV. Linking HIV prevention and family planning strategies for this age group may help minimize the number of infants with poor birth outcomes among this already vulnerable population.